Pesan-Pesan Dakwah dalam Film 3 Idiots - el Ishaq, Ropingi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2016)
The 3 Idiots is a movie of India. This movie has launched at 2009th and as a favorite movies in Bollywood. The 3 Idiots get appreciate of international movies. Itâ€™s movies adopt from best seller of novel by Chetan Bhagat, â€œFive Point Someoneâ€. The 3 Idiots bring the social criticism about social and cultural, like about social value. By that argue, this study aims to explore the sign and message of Islamic value in the movies. Qualitative approach used in this study. Specially, semiotic analysis of Ferdinand De Saussure use in this study. Both point of Ferdinand De Saussure semiotic are; signifier and Signified, Langue and Parole, so Syntagmatic and Associative. For message analysis of daâ€™wa will be doing to explore an message of daâ€™wa in the movies. Itâ€™s movies share an five message of daâ€™wa; first, theologies as such represented how to motivate about awareness to God. Second, about the education, as such the criticism for education system. Thirt, the solidarity. In solidarity does explore how to help to brother or friends. Fourd, a harmony of religiousity. Five, amar maâ€™ruf nahi munkar or the motivated to do the possitive value and then be counter to negative value. The messages did constructed as beautifully. Signifier and signified or symbol had used to represent of meaning. The langue and parole has constructed with syntagmatic and association for to present the grand message, as such â€˜idiots attitudeâ€™. All signs constructed systematically and beautifully. So, the audience can to get the meaning.